Three-dimensional magnetic fields of molecular clouds - Tahani, Mehrnoosh (Frontiers in Astronomy and Space Sciences, 2022)
To determine the role of magnetic fields in the formation and evolution of molecular clouds, and ultimately the formation of stars, their three-dimensional (3D) magnetic fields must be probed. Observing only one component of magnetic fields (along the line of sight or parallel to the plane of the sky) is insufficient to identify these vectors in three dimensions. In recent years, novel techniques for probing each of these two components and integrating them with additional data (from observations or models), such as Galactic magnetic fields or magnetic field inclination angles, have been developed, in order to determine 3D magnetic fields. We review and discuss these advancements, their applications, and their future direction.